Ekonomi Kreatif: Pemetaan Kendala dan Analisis Strategi Kebijakan Pemerintah Studi Kasus pada Kota Bengkalis - Tri Handayani; Rini Arvika Sari (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2020)
This study aims to explain the creative economy phenomenon in Bengkalis City, explain the existing obstacles from the aspects of Administration, Technical, Operations and Management of Creative Industry entrepreneurs, analyze interventions through policies that have been carried out by the government, then describe development strategies that can be carried out by the Bengkalis government. The Research method was exploratory, where the process of mapping the obstacles in the creative economy industrial applications using purposive sampling technique that involves creative Indutri players. then doing descriptive analysis techniques related to government policies and strategies in developing the creative economy in Bengkalis City. The results of the Mapping constraints are from the aspek of ATOM (Administration, Technical, Operasional, anda Management) shows the constraints most felt by Creative Industry players, namely regulation of raw materials, especially the industrial subsector that relies on natural resources (administrative aspecst), high risk due to product failure (goods/ services) offered to the market (technical aspects), the scarcuty and high cost of raw materials to produce their business product (operasional aspects), and the existence of limited creative economy business in getting skilled employees who want to pursue the creative work of the business (management aspects). A number of breakthroughs that have been taken by the government are by implementing provincial or regional scale policies, which provide business protection, create business climate, and develop the creative economy. As well as creating the Riau Creative Network Agency to further optimize the development of the creative economy and aspects of its promotion. The development strategy needs to be done which has the aim so that the existing policies and strategies are more adaptive according to the needs of the city of Bengkalis and respond to existing challenges and constraints.